FAKTOR LINGKUNGAN INTERNAL PENGHAMBAT UTILISASI E-COMMERCE PADA UMKM: Studi Kasus pada UMKM Kerajinan di Kabupaten Bantul - Setyo, Mohamad Aji; Fitriani*, Syifa (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
The growth of e-commerce in Indonesia has become very rapid and fast which has resulted in many marketplaces starting to emerge and not directly changing consumer shopping behavior. Seeing this, Micro, Small and Medium Enterprises (MSMEs) must be able to adapt and start using e-commerce, but in its application there are several internal obstacles that are experienced. If these obstacles are not immediately resolved, it will have an impact on the progress of MSMEs themselves. The purpose of this study was to determine the effect of the internal environment on barriers to the use of e-commerce. The method used in this research is multiple linear regression. From the results of research with a number of respondents as many as 110 MSMEs, it can be ascertained that human and financial resources have a significant effect on the implementation of e-commerce, while the product variable has no significant effect on inhibiting the use of e-commerce. From these results, it is important for MSMEs to improve their human and financial resource expertise so that they can successfully use e-commerce. Keywords: E-commerce, MSMEs, Barriers, Internal Environmental Factor, Multiple Linear Regression